2017
DOI: 10.1002/ejhf.775
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of β‐blocker selectivity and dosage regimens in heart failure patients. Insights from the MECKI score database

Abstract: In a large population of chronic HFrEF patients, β-blockers were associated with a more favourable prognosis without any difference between β1- and β2-receptor-blockers vs. β1-selective blockers. A better outcome was observed in subjects receiving a high daily dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…Finally, we also evaluated the role of daily β-blocker dose, grouping patients according to carvedilol-equivalent dose (group 1 ≤ 12.5 mg/day, group 2 >12.5-≤25 mg/day and group 3 > 25 mg/day). The carvedilol-equivalent dose was calculated for nebivolol and bisoprolol as dose x 5, and for metoprolol as dose/4 [17,22]. Again, Kaplan-Meyer survival curves were normalized for the same confounding factors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, we also evaluated the role of daily β-blocker dose, grouping patients according to carvedilol-equivalent dose (group 1 ≤ 12.5 mg/day, group 2 >12.5-≤25 mg/day and group 3 > 25 mg/day). The carvedilol-equivalent dose was calculated for nebivolol and bisoprolol as dose x 5, and for metoprolol as dose/4 [17,22]. Again, Kaplan-Meyer survival curves were normalized for the same confounding factors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, the effects of β-blockers on survival in HF patients is dose-dependent, so that the higher the dose, the better the survival rate [17][18][19][20]. Unfortunately, the β-blocker dose is unknown, at least in most of the studies on HF patients with atrial fibrillation, and this generates a further theme of uncertainty.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk associated with a 1 mL/kg/min decrease in pVO 2 is 50% lower with beta‐blockers . The MECKI investigators reported a 43% adjusted lower risk of cardiovascular death/urgent transplant with beta‐blocker use, although this important variable is not included in the MECKI model. Women have a lower risk of death for the same pVO 2 in many cohorts.…”
mentioning
confidence: 99%
“…It was confirmed the better survival of patients on β‐blockers without, however, differences depending on the type of β‐blocker administered. Patients receiving higher β‐blocker doses had better outcomes …”
Section: Medical Therapymentioning
confidence: 95%